Perlindungan Hukum Pelaku Usaha Lelang Tiktok Shop Atas Tindakan Bid and Run - Fernando Tantaru; Teng Berlianty; Sarah Selfina Kuahaty (PAMALI: Pattimura Magister Law Review, 2023)
Introduction: In connection with the development of information and communication technology, one of which is the Tiktok Shop, where goods or services can be traded to consumers across regional boundaries, consumer protection is an important matter that must be considered. In this regard, consumer protection is more heavily regulated compared to business actors, who often experience losses through bidding and running,Purposes of the Research:  The purpose of this study is to analyze and discuss legal protection for business actors and consumer legal liability in bid and run defaults in tiktok shop auctions.Methods of the Research: The research method used is normative legal research and a legal concept analysis research approach using library research collection techniques.Results of the Research: The existence of legal protection can provide legal certainty for various problems faced by society. If consumers take bid and run that have clearly violated the agreement, consumers have violated the right of business actors to receive payments in accordance with the agreement regarding the conditions and exchange rates of goods and services sold.